AKURASI INFORMASI DENGAN MENGGUNAKAN TEKNOLOGI RFID PADA PENGENDALIAN PERSEDIAAN BARANG DI SUPERMARKET - Rindra Yusianto (Semantik, 2011)
Abstract Internal problems supermarket is periodic stock taking activities by checking each item on the shelves of sales, management policy to maximize the functions of warehouse management and ignorance about the current amount of goods in real time. This often causes delays in shipments, resulting in the occurrence of stockouts. In addition, management ignorance about the current amount of goods in real time allows bookings again for the goods that are physically adequate amount of stock still. So this results in over-stock. This study is purely experimental, is research that is done by making a prototype of a tested, pre and post test. In this research, design and build to optimize RFID inventory control, in this case, minimizing stockouts and stock taking into consideration factors over the accuracy of the information. The main result is the accuracy of information after use of RFID technology are better than before using RFID technology.Keywords : accuracy of information, RFID, inventory, supermarket